EFFECT OF PROCESS PARAMETERS AND INJECTOR POSITION ON THE EFFICIENCY OF NOX REDUCTION BY SELECTIVE NON CATALYTIC REDUCTION TECHNIQUE - Hamid, A.; Mehmood, M. A.; Irfan, N.; Javed, M. T.; Waheed, K. (The Nucleus, 2020)
An experimental investigation has been performed to study the effect of atomizer pressure dilution of the reducing reagent and the injector position on the efficiency or the NOx reduction by a selective non-catalytic reduction technique using urea as a reducing agent. Experiments were performed with a flow reactor in which flue gas was generated by the combustion of methane in air at stoichiometric amount of oxygen and the desired levels of initial NOx (400-450 ppm) were achieved by doping the flame with ammonia. The work was directed to investigate the effect of atomizer pressure, dilution of urea reagent and the injector position. The atomizer pressure was varied from 1 to 3bar and 20-25% increase in efficiency was observed by decreasing the pressure. Effect of dilution of urea solution was investigated by varying the strength of the solution from the 8 to 32% and 40-45% increase in the efficiency was observed. Effects of injector position was investigated by injecting the urea solution both in co current and counter current direction of the flue gases and 20-25% increase in the efficiency was observed in counter current direction.